2022
DOI: 10.3390/foods11193048
|View full text |Cite
|
Sign up to set email alerts
|

Monascuspiloin from Monascus-Fermented Red Mold Rice Alleviates Alcoholic Liver Injury and Modulates Intestinal Microbiota

Abstract: Monascus-fermented red mold rice (RMR) has excellent physiological efficacy on lipid metabolism and liver function. This study investigated the ameliorative effects of monascuspiloin (MP) from RMR on alcoholic liver injury in mice, and further clarified its mechanism of action. Results showed that MP intervention obviously ameliorated lipid metabolism and liver function in mice with over-drinking. In addition, dietary MP intervention reduced liver MDA levels and increased liver CAT, SOD, and GSH levels, thus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Lachnospiraceae and Muribaculaceae produce butyrate, which are powerful indicators of a healthy intestinal, produced butyrate [56][57][58]. A related report revealed that the incidence of ALD was significantly correlated with the abundance of Lachnospiraceae and Muribaculaceae [59]. Un-cultured_bacteria_f_Lachnospiraceae and Lachnospiraceae_NK4A136_group were reported to have the potential ability to enhance the host antioxidant capacity [60], which coincides with the positive correlation between antioxidant indices observed in this investigation.…”
Section: The Effect Of Ayp On the Intestinal Bacteria Of Micementioning
confidence: 60%
“…Lachnospiraceae and Muribaculaceae produce butyrate, which are powerful indicators of a healthy intestinal, produced butyrate [56][57][58]. A related report revealed that the incidence of ALD was significantly correlated with the abundance of Lachnospiraceae and Muribaculaceae [59]. Un-cultured_bacteria_f_Lachnospiraceae and Lachnospiraceae_NK4A136_group were reported to have the potential ability to enhance the host antioxidant capacity [60], which coincides with the positive correlation between antioxidant indices observed in this investigation.…”
Section: The Effect Of Ayp On the Intestinal Bacteria Of Micementioning
confidence: 60%
“…The biological activity of the Monascus sp. DBM 4361 major yellow MP—monascuspiloin has only partly been investigated in biological activity studies not related to its antimicrobial activity (just the study targeted to improvement of alcoholic liver injury of mice [ 45 ] and the study focussed on combination ionizing radiation and monascuspiloin administration in human prostate cancer therapy [ 46 , 47 ]).…”
Section: Discussionmentioning
confidence: 99%
“…In order to analyze the intervention mechanism of CASP on the liver injury from the perspective of the intestine, the 16S rDNA amplicon sequencing technology was carried out. Intestinal flora is closely related to liver injury [ 20 ].…”
Section: Discussionmentioning
confidence: 99%